C. elegans flavin-containing monooxygenase-4 is essential for osmoregulation in hypotonic stress - Hirani, Nisha (Biol Open, 2016)
Studies in Caenorhabditis elegans have revealed osmoregulatory systems engaged when worms experience hypertonic conditions, but less is known about measures employed when faced with hypotonic stress. Inactivation of fmo-4, which encodes flavin-containing monooxygenase-4, results in dramatic hypoosmotic hypersensitivity; worms are unable to prevent overwhelming water influx and swell rapidly, finally rupturing due to high internal hydrostatic pressure. fmo-4 is expressed prominently in hypodermis, duct and pore cells but is excluded from the excretory cell. Thus, FMO-4 plays a crucial osmoregulatory role by promoting clearance of excess water that enters during hypotonicity, perhaps by synthesizing an osmolyte that acts to establish an osmotic gradient from excretory cell to duct and pore cells. C. elegans FMO-4 contains a C-terminal extension conserved in all nematode FMO-4s. The coincidently numbered human FMO4 also contains an extended C-terminus with features similar to those of FMO-4. Although these shared sequence characteristics suggest potential orthology, human FMO4 was unable to rescue the fmo-4 osmoregulatory defect. Intriguingly, however, mammalian FMO4 is expressed predominantly in the kidney – an appropriate site if it too is, or once was, involved in osmoregulation.